Analisis Collaborative Governance Dalam Penerapan Elektronik Kesehatan (E-Kes) Di Kabupaten Bengkulu Tengah - Deni Triyanto; Soehito Efendi; Veny Puspita (Universitas Medan Area, 2021)
The purpose of this research is to analyze collaborative governance in the application of e-kes in Bengkulu Tengah Regency, using descriptive qualitative research methods with indicators of network structure, commitment to a common purpose, trust among the participants, and access to resources